Estudo da associação das condições periodontais e o espessamento do complexo intimal de carótida - Batista, Rafaela das Mercês (2010)
This dissertation is presented in the form of articles. The work presented in this study discussed the interdisciplinary team work in studies that propose to investigate the association of oral conditions and systemic conditions, the heterogeneity of periodontal indices used in epidemiological studies and the association between periodontal disease (PD) and thickening of the intimal (IMT) of carotid arteries. The first article is a literature review that aims to discuss the role of interdisciplinary in research studying the possible association between oral conditions and systemic implications. The second article, a cross-sectional analysis of periodontal clinical measurements to test four models of protocols for measuring partial-mouth. The third, a systematic review of PD and subclinical atherosclerosis. The room is a crosssectional study of association of clinical measures of PD and carotid IMT. The first study found that it is necessary to the inseparable aspects of oral health and overall health of the individual, emphasizing the importance of knowledge through information exchange. Thus, the information enables the meeting of various professional performances through integrated actions more objective and effective in the search for quality information that portrays the most favorable way possible the actual conditions of health of the individual and collective. The second article emphasized in its findings that it is desirable that further studies, ideally all, examine all sides of all teeth even if this approach is obviously the most laborious, but reveal more precisely the epidemiology of periodontal disease among adults. The systematic review showed that many studies did not control for confounders and there was a clear heterogeneity among studies on how periodontal disease was measured and on what type of measure of subclinical atherosclerosis was used as the outcome. The limitations in methodologies used in most studies do not allow reliable conclusions to be drawn about real associations between periodontal disease and subclinical atherosclerosis. A cross sectional study on ELSA adults participants aged 35-74years (n= 220) was conducted on the association of clinical measures of PD and intima media wall thickness of the carotid artery. The clinical results showed that levels of thickening of carotid intima-media were higher in the groups with severe PD than in the groups without PD. The cases of thickening of carotid intima-media had a tendency to have higher levels of severe PD compared to those without PD when the extent of more than 30% of sites with attachment level ≥ 5 mm was used. The DP did not increase the risk for subclinical atherosclerosis after multivariate regression, since the age was a confounding factor in this time of adjustment. In conclusion, periodontal disease was not a risk factor for atherosclerosis in ELSA-ES study adults.